Synthesis and Characterization of the First Cyrhetrenyl-Appended Calix[4]Arene Macrocycle and Its Application as an Electrochemical Sensor for the Determination of Cu(Ii) in Bivalve Mollusks Using Square Wave Anodic Stripping Voltammetry - Segura-Segura, R; Segura-Segura, R; Godoy-Gonzalez, F; Godoy-Gonzalez, F; Maldonado-Hernandez, T; Maldonado-Hernandez, T; Pizarro-Reyes, J; Pizarro-Reyes, J; Flores-Vergara, E; Flores-Vergara, E (Elsevier B.V., 2019)
An electrochemical sensor for the determination of Cu(II) in bivalve mollusks using a glassy carbon electrode modified with p-tert-butylcalix [4]arene-bis-cyrhetrenylimine (Cy2(Calix [4])) by square wave anodic stripping voltammetry (SWASV) has been developed. The organometallic compound was synthesized from cyrhetrene-carboxaldehyde and 25,26-bis-(2-aminoethoxy)-26,28-dihydrocalix [4]arene through a condensation reaction. Metalloligand (Cy2(Calix [4])) was characterized by FT-IR and 1H-13C 2D NMR spectroscopies and monocrystal X-ray diffraction and was obtained as a single isolated isomer (E). The optimum chemical and electrochemical conditions for the modified electrode were optimized and the methodology was applied in different samples of bivalve mollusks with satisfactory results. A cooperative effect between the organometallic fragment and the calixarene macrocycle improves the preconcentration capacity of the electrochemical sensor, creating a new opportunity to perform rapid and sensitive analyses in the detection of copper in marine resources. © 2018 Elsevier B.V.